Transformation Towards a Sharia-Based Economy: Theory, Practice and Social Implications - Arum Khairunnisa; Muhammad syam'ani; Rahma putri widyaningsi; Anna Tiara Rahma; Eko Nursalim (Penerbit Hellow Pustaka, 2025)
Sharia economics is an economic paradigm based on Islamic principles, which includes aspects of finance, investment and distribution of wealth by complying with Islamic laws. This concept emphasizes fairness, transparency and sustainability in various economic activities. In this journal, we will explore several key aspects of Islamic economics from a theoretical and practical implementation perspective. Sharia economic theory integrates Islamic principles into the existing economic framework. One of the main principles is the prohibition of usury (riba al-duyun), which prohibits the practice of interest in the financial system. This encourages the development of alternative financial instruments such as mudharabah (profit sharing) and murabahah (buying and selling with a markup). (Amalia 2020). Apart from that, the sharia economic concept also emphasizes distributive justice, where wealth and natural resources must be distributed fairly among society. These principles are reflected in zakat (religious donations) and sadaqah (voluntary donations), which are important instruments in the redistribution of wealth to overcome social inequality